A dynamic model of a Cardan joint to evaluate the effect of elasticity and manufacturing errors. Issue 1 (24th February 2021) - Cirelli, Marco; Rossi, Valerio; Valentini, Pier Paolo; Pennestrì, Ettore
Cardan joint is a key component in many mechanical applications. Due to the redundancy of kinematic constraints, the accurate determination of reaction forces and the assessment of dynamic effects caused by joint tolerances are very challenging tasks. This paper presents a computer-aided multibody modelling approach for the simulation of a Cardan joint with manufacturing errors. During the modelling phase, the elasticity of flexible bodies is lumped and the joint compliance is taken into account using concentrated non-linear spring elements. Numerical examples have been developed and discussed in order to test the feasibility of the proposed methodology.